New species of palaearctic Oribotritiidae (Acari, Oribatida) - Niedbała, Wojciech (Zootaxa, 2006)
Seven new Palaearctic species of the oribatid mite family Oribotritiidae are described: Oribotritia baikalica sp. nov. from Russia, O. shikoku sp. nov. from Japan, O. schusteri sp. nov. and O. turcica sp. nov. from Turkey, O. tashkentae sp. nov. from Uzbekistan, Maerkelotritia kirghizica sp. nov. from Kyrgizstan and Indotritia tricarinata sp. nov. from Slovenia.